INFLUENCE OF TEMPERATURE AND SOLAR RADIATION ON THE POWER OF PHOTOVOLTAIC PANELS - З. М. Игамкулова (European Science Publishing, 2024)
This paper examines an equivalent panel circuit and simulates in a MATLAB environment using standard photovoltaic panel data, and investigates the effects of temperature and solar radiation on the power and volt-ampere performance of a photovoltaic panel. Despite great advances in semiconductor material technology, the efficiency of panels has remained quite low in recent years. The efficiency of the panel is affected by many factors, such as tilt angle, shading, dust, solar radiation levels, temperature, and conductor losses. Among these factors, solar radiation levels and temperature are more important. The level of solar radiation reaching photovoltaic panels varies depending on the location of the panel and the time intervals per day. Thus, the level of solar radiation directly affects the power of the panel. As a result, a decrease in the level of solar radiation reduces the power of the panel. On the other hand, there is an inverse relationship between the temperature and the power of the panel. In this paper, we developed a model of photovoltaic panels in the Matlab/Simulink program depending on the basic photovoltaic cell substitution scheme, taking into account environmental factors such as solar radiation and temperature
Keywords: solar energy; angle of inclination; annual optimal angle of inclination, monthly angle of inclination, solar radiation.